ANALYSIS OF CLOUD COMPUTING INFRASTRUCTURE SYSTEM WITH NIST STANDARD CLOUD COMPUTING STANDARDS ROADMAP - Gautama Wijaya; Avian Avian (Universitas Internasional Batam, 2022)
Cloud computing is a computing model that provides easy access to computing resources in the form of services. Cloud computing describes an operational and economic model for the provision of it infrastructure and related services. This thesis aims to test the on premise infrastructure at pt. In this study, the aspects tested include, on-demand-self-service, broad network access, resource pooling, rapid elasticity, measured service, virtualization, browser as a platform, free and open source software, web 2.0 support, and utility computing. . The research method used here is a direct test method on the existing infrastructure at PT. XYZ.